Synergetic Effect of rHDL and LXR Agonist on Reduction of Atherosclerosis in Mice - Morin, Emily E.; Guo, Yanhong; He, Hongliang; Yuan, Wenmin; Souery, Whitney N.; Fawaz, Maria V.; Chen, Yuqing Eugene; Schwendeman, Anna (Frontiers in Pharmacology, 2020)
High-density lipoproteins (HDLs) are unique in that they play an important role in the reverse cholesterol transport process. However, reconstituted HDL (rHDL) infusions have demonstrated limited beneficial effect in clinical practice. This is perhaps a consequence of the limited cholesterol efflux abilities of atheroma macrophages due to decreased expression of cholesterol transporters in advanced atheromas and following rHDL infusion treatment. Thus, we propose that a combination therapy of rHDL and a liver X receptor (LXR) agonist could maximize the therapeutic benefit of rHDL by upregulating ATP-binding cassette transporters A-1 (ABCA1) and ATP-binding cassette transporter G-1 (ABCG1), and enhancing cholesterol efflux to rHDL. In macrophages, rHDL downregulated the expression of ABCA1/G1 in a dose- and rHDL composition-dependent manner. Although LXR agonist, T0901317 (T1317), upregulated the expression of ABCA1 and ABCG1, the drug itself did not have any effect on cholesterol efflux (6.6 ± 0.5%) while the combination of rHDL and T1317 exhibited enhanced cholesterol efflux from [3H]-cholesterol loaded J774A.1 macrophages (23.3 ± 1.3%). Treatment with rHDL + T1317 significantly reduced the area of aortic plaque in ApoE−/− mice compared to PBS treated control animals (24.16 ± 1.42% vs. 31.59 ± 1.93%, p < 0.001), while neither rHDL nor T1317 treatment alone had a significant effect. Together, we show that rHDL paired with an LXR agonist can induce a synergetic effect in reducing atheroma burden. This synergy could lead to lower overall effective dose for both drugs, potentially overcoming the existing barriers in clinical development and renewing pharmaceutical interest in these two drug classes.